TRmir: A Comprehensive Resource for Human Transcriptional Regulatory Information of MiRNAs - Gao, Yu; Feng, Chenchen; Zhang, Yuexin; Song, Chao; Chen, Jiaxin; Li, Yanyu; Wei, Ling; Qian, Fengcui; Ai, Bo; Liu, Yuejuan; Zhu, Jiang; Su, Xiaojie; et al. (Frontiers in Genetics, 2022)
MicroRNAs (miRNAs) are small non-coding RNAs, which play important roles in regulating various biological functions. Many miRNA databases available have provided a large number of valuable resources for miRNA investigation. However, not all existing databases provide comprehensive information regariding transcriptional regulatory regions of miRNAs, especially, typical-enhancer, super-enhancer (SE) and chromatin accessibility regions. An increasing number of studies have shown that transcriptional regulatory regions of miRNAs, as well as related single nucleotide polymorphisms (SNPs) and transcription factors (TFs), have a strong influence on human diseases and biological processes. Here, we developed a comprehensive database for human transcriptional regulation of miRNAs (TRmir), which is focused on providing a wealth of available resources regarding transcriptional regulatory regions of miRNAs and annotating their potential roles in the regulation of miRNAs. TRmir contained a total of 5,754,414 typical-enhancers/SEs and 1,733,966 chromatin accessibility regions associated with 1,684 human miRNAs. These regions were identified from over 900 human H3K27ac ChIP-seq, ATAC-seq and DNase-seq samples. Furthermore, TRmir provided detailed (epi) genetic information about transcriptional regulatory regions of miRNAs, including TFs, common SNPs, risk SNPs, linkage disequilibrium (LD) SNPs, expression quantitative trait loci (eQTLs), 3D chromatin interactions and methylation sites, especially supporting the display of TF binding sites in the regulatory regions of over 7,000 TF ChIP-seq samples. In addition, TRmir integrated miRNA expression and related disease information, supporting extensive pathway analysis. TRmir is a powerful platform that offers comprehensive information about transcriptional regulation of miRNAs for users and provides detailed annotations of regulatory regions. TRmir is free for academic users and can be accessed at http://bio.liclab.net/trmir/index.html.